Fruit morphological characteristics of cultivated Aquilaria lam. (Thymelaeaceae) in Peninsular Malaysia - Pern, Y. C.; Lee, Shiou Yih; Ludin, R.; Mohamed, Rozi (Jabatan Perhutanan Semenanjung Malaysia, 2018)
The agarwood-producing tree, Aquilaria spp. was recently domesticated and largely cultivated for the purpose of sustainably producing agarwood in Malaysia. In this study, fruit morphological characteristics of five Aquilaria species commonly cultivated in Peninsular Malaysia are reported. Each species has significant fruit or capsule characteristics that could be used in speciesidentification: Aquilaria crassna - huge and wrinkled, Aquilaria hirta - velvety and obtuse calyx lobes, Aquilaria malaccensis - paper-like texture and triangular calyx lobes, Aquilaria sinensis - diamond-shaped and oblong calyx lobes, and Aquilaria subintegra - fine hairs and rounded calyx lobes. These features are significant taxonomic characteristics for differentiating the five species.